Cyclic di‐GMP inhibits Vibrio cholerae motility by repressing induction of transcription and inducing extracellular polysaccharide production. Issue 6 (8th November 2013) - Srivastava, Disha; Hsieh, Meng‐Lun; Khataokar, Atul; Neiditch, Matthew B.; Waters, Christopher M.
Summary Cyclic di‐GMP (c‐di‐GMP) controls the transition between sessility and motility in many bacterial species. This regulation is achieved by a variety of mechanisms including alteration of transcription initiation and inhibition of flagellar function. How c‐di‐GMP inhibits the motility of Vibrio cholerae has not been determined. FlrA, a homologue of the c‐di‐GMP binding Pseudomonas aeruginosa motility regulator FleQ, is the master regulator of the V. cholerae flagellar biosynthesis regulon. Here we show that binding of c‐di‐GMP to FlrA abrogates binding of FlrA to the promoter of the flrBC operon, deactivating expression of the flagellar biosynthesis regulon. FlrA does not regulate expression of extracellular Vibrio polysaccharide (VPS) synthesis genes. Mutation of the FlrA amino acids R135 and R176 to histidine abrogates binding of c‐di‐GMP to FlrA, rendering FlrA active in the presence of high levels of c‐di‐GMP. Surprisingly, c‐di‐GMP still inhibited the motility of V. cholerae only expressing the c‐di‐GMP blind FlrA(R176H) mutant. We determined that this flagellar transcription‐independent inhibition is due to activation of VPS production by c‐di‐GMP. Therefore, c‐di‐GMP prevents motility of V. cholerae by two distinct but functionally redundant mechanisms.